Innovating EFL Teaching in Asia - Muller, Theron. author. aut Link
XXIV, 301 p.
Keywords: This collection offers a distinctly Asian voice for English language education and addresses some of the unique needs of Asian learners in EFL contexts. Teachers and researchers from nine Asian countries present some of the most current and innovative research in five distinct and fascinating areas of EFL teaching and learning.